Graphene-Palladium catalysed exhaust gas reformer system - Rahman, Mohammed Ataur (2017)
The present invention relates to an exhaust gas reforming system (1) for providing hydrogen gas as fuel additive to an internal combustion engine (2) comprising a reformer (3) having a first zone (3a) for mixing the exhaust gas and steam, and a second zone (3b) for generating reformed hydrogen gas and comprising a catalyst (4) having a composition of 20-40 wt% palladium and 60-80 wt% graphene; and a steam generator (5), in which steam is produced using the hot exhaust gas released from the internal combustion engine (2). According to the present invention, the catalyst (4) can improve the efficiency of exhaust gas reforming process and thereby increase the yield of hydrogen gas. By utilizing the exhaust gas reforming system (1) of the present invention that feeds the reformed hydrogen gas into the engine (2) as fuel additives, fossil fuel consumption can be reduced. Therefore, the present invention provides a solution towards better fuel economy and reduction of greenhouse gas emission.